Cardiovascular disease, depression and mortality: The health in men study - Almeida, O.; Alfonso, Helman; Flicker, L.; Hankey, G.; Norman, P. (2012)
Background: Existing evidence from observational studies suggests that cardiovascular diseases (CVD) and depression may be causally related, although the direction of this association and its etiologic relevance remain uncertain. One way to further elucidate the nature of this relationship is by determining the joint effect of CVD and depression on a common outcome, such as mortality. Aims: To determine if CVD and depression interact to increase mortality in older men. Methods: This cohort study followed 4,805 older men for 6.0 years or until death using administrative record linkage information. At the time of entry into the study, participants provided systematic information about prevalent peripheral arterial disease, and coronary heart disease, and history of past stroke. Men with any of these conditions were considered to have CVD. Participants with a total score of 7 or more on the 15-item Geriatric Depression Scale were classified as depressed. Sociodemographic and clinical data were obtained using standard procedures. Results: Men with CVD had greater mortality hazard than men without CVD (HR = 1.5, 95% CI = 1.3-1.7), and men with depression had greater mortality hazard than men without depression (HR = 1.8, 95% CI = 1.3-2.6). The interaction between depression and CVD had no obvious effect of mortality (HR = 1.0, 95% CI = 0.6-1.5). All analyses were adjusted for age, education, living arrangements, Duke Social Support grouping, smoking, and history of diabetes, hypertension, and dyslipidemia. Conclusion: Depression and CVD do not interact to increase mortality, which suggests that the successful management of CVD is unlikely to reduce mortality attributed to depression, and vice-versa. © 2012 American Association for Geriatric Psychiatry.